2022
DOI: 10.1002/ejp.1909
|View full text |Cite
|
Sign up to set email alerts
|

Gold micro‐particles for knee osteoarthritis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 57 publications
0
18
1
Order By: Relevance
“…No SAE was reported. Another clinical study showed that intra-articular gold microparticles injection in knee osteoarthritis joints relieved perceived pain of OA patients [ 14 ]. The results from these two clinical studies in OA patients are consistent with the results from the present study in both RA and OA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No SAE was reported. Another clinical study showed that intra-articular gold microparticles injection in knee osteoarthritis joints relieved perceived pain of OA patients [ 14 ]. The results from these two clinical studies in OA patients are consistent with the results from the present study in both RA and OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent open-label study with 63 osteoarthritis (OA) patients, intra-articular gold injection improved their Knee injury and Osteoarthritis Outcome Score (KOOS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, with no reported severe adverse effects (SAE) [ 13 ]. In another newly published exploratory clinical study, gold microparticles injected intra-articularly in osteoarthritic knee joints relieved perceived pain and generated an inflammation modulatory effect based on proteome changes found in synovial fluid SF and serum [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies do support the role of inflammation in the pathogenesis of osteoarthritis including nodal osteoarthritis of the hand [9,10]. Injection of gold microparticles directly into osteoarthritic knee joints may provide pain relief and improved joint function [11]. The use of gold-based autologous conditioned serum injection into affected joints is now being explored as a treatment in osteoarthritis [12].…”
Section: Clinical Image Peer Reviewed | Open Accessmentioning
confidence: 99%
“…We evaluated pain and function at baseline and at a two-year follow in two groups of patients with painful KOA. One group, I, received intra-articular 20 mg gold micro-particles using the patient's synovial uid (SF) as the carrier [4]. The other group, II, received intra-articular 20 mg gold micro-particles using hyaluronic acid (HA) as the carrier.…”
Section: Study Owmentioning
confidence: 99%
“…During the inclusion of our open pilot study, we excluded a larger group of KOA patients due to multisite pain, co-morbidities, and other exclusion criteria [4]. This group received intra-articular gold microparticles using hyaluronic acid, whereas the included group received the treatment using the patient's synovial uid.…”
Section: Introductionmentioning
confidence: 99%